Reformed identity revisited: Proposals in the spirit of Ecclesia Semper Reformanda est - Nico Vorster (In die Skriflig, 2020)
This article commences by reflecting on the evolving nature of traditions. In order to pass the continual test of plausibility and authenticity, traditions need to be flexible enough to incorporate new insights into its core intellectual matrix. Implausible elements need to be re-articulated or dispensed with. This rationale is subsequently applied to the reformed tradition who considers the necessity to continually reform itself (Ecclesia Semper Reformanda est) as a fundamental aspect of the tradition. Recently, various tenets of the reformed faith have come under scrutiny. These include the reformed faith’s understanding of God’s relation to creation; its view of human uniqueness; its understanding of original sin and the transmission of sin; and its supposed sola Scriptura approach to ethics. This article addresses these critiques by proposing that reformed theology incorporates the notion of creation as a gift in its thinking; that it dispenses with attempts to provide a historical narrative on the origin and transmission of sin and rather approach the theme from an existential perspective; and that it works towards an ethics that is scripturally based but ecclesiastically shaped.